The Use Two Methods of Presentation Clarity and Individual Competition to Develop of Mental Energy Mobilization and Learn Some Basic Skills for Students in Football - Khalil Hamid Mohammed Ali (Journal of Global Pharma Technology, 2016)
Through the follow-up of field researchers to teach football in the lesson of physical education, he noted that many of the learners have difficulty in learning the basic skills as a result of their teaching methods, and that teaching requires other methods that lead to the best possible learning in accordance with the development of the game This is reflected in the upgrading of this game. The researchers' interest in this problem began in an attempt to reveal the use of methods to develop psychic energy and to learn the basic skills of football for students better. The objective of the research is to:Preparation of an educational program using the method of clarity of presentation in the development of mental energy mobilization and learn some basic skills for students of footballPreparation of an educational program using the method of individual competition in the development of mental energy mobilization and learn some basic skills for students of football.Identify which method (s) used best in the development of mental energy mobilization and learn some basic skills for football students.The Main Conclusions WereA clear improvement in the development of (experimental groups in the measure of mental energy mobilization and learn some of the basic skills of football.The first experimental group (individual competition mode) is superior to the second experimental group (the method of presentation clarity) in the development of the mental energy mobilization scale.The second experimental group (the clarity of presentation) has learned to teach the first experimental group (the style of individual competition) in the basic skills of football.Keywords: Two methods clarity of presentation and individual competition and the mobilization of psychological energy.